2021
DOI: 10.1007/s00404-021-06331-0
|View full text |Cite
|
Sign up to set email alerts
|

Video colposcopy versus headlight for large loop excision of the transformation zone (LLETZ): a randomised trial

Abstract: Purpose To compare resected cone mass and resection margin status when performing Large Loop Excision of the Transformation Zone (LLETZ) using video colposcopy (LLETZ-VC) versus a headlight (LLETZ-HL) in women with cervical dysplasia. Methods Prospective, randomised trial (monocentric) at a specialised cervical dysplasia unit in a University Hospital. Women with a biopsy-proven CIN2 + or persisting CIN1 or diagnostic LLETZ were recruited and randomised. LL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Using the remaining 37 citations, cross reference searching identified two further appropriate citations. Thus, in summary, 39 citations reporting on diagnostic and therapeutic interventions in women with cervical dysplasia within a controlled trial setting were included in this review [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Among them, we found 5 PCTs [ 13 , 14 , 15 , 16 , 17 ] and 28 RCTs [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the remaining 37 citations, cross reference searching identified two further appropriate citations. Thus, in summary, 39 citations reporting on diagnostic and therapeutic interventions in women with cervical dysplasia within a controlled trial setting were included in this review [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Among them, we found 5 PCTs [ 13 , 14 , 15 , 16 , 17 ] and 28 RCTs [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , …”
Section: Resultsmentioning
confidence: 99%
“…The clinical characteristics of individual studies reporting on therapeutic procedures in women with cervical dysplasia are shown in Table 2 . We identified 20 RCTs with 3355 participants [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and one PCT with 297 participants [ 17 ]. in total, 4 RCTs found that alternative electrosurgical techniques such as Straight Wire Excision of the Transformation Zone (SWETZ), Contour-Loop Excision of the Transformation Zone (C-LETZ), and True Cone Biopsy Electrode Excision (TCBEE) were comparable to the standard LEEP/LLETZ procedure with minimal differences regarding specimen fragmentation and endocervical resection margin status [ 26 , 27 , 28 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations